(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study was designed to examine the relationship between human capital management and organizational performance ty.ectiveness in organization’toor management of personnel.ibilities , assignment of the right jobs to wrong and unqin United Bank for Africa Plc, Uyo, Akwa Ibom State. To achieve this objective, survey research design was adopted for this study. The population of the study consisted of management staff, senior staff and junior staff of the United Bank for Africa Plc. Uyo, Akwa Ibom State which is made up of 82 staff with sample size of 68 staff. The study utilized Taro Yamane Scientific technique. The instrument used for data collection was Human Capital Management and Organizational Performance Questionnaire (HCMOPQ). Tables, Mean, Standard Deviation and Pearson Product Moment Correlation Coefficient were adopted as analytical tools for this study. Two hypotheses were tested at 0.05 level of significance. The result of the study showed that there was a positive significant relationship between human capital management and organizational performance in United Bank for Africa Plc, Uyo, Akwa Ibom State. The result of the findings also revealed that organizational performance is dependent on the extent of its staff training and timely appraisal of employees. This implies that increased investment in staff training and timely appraisal of employees by the bank would yield greater returns in organizational performance.